Remediation program with automatized naming and reading for students with dyslexia: Elaboration and clinical significance - Dos Santos, Bianca [UNESP] (2020)
Purpose: Elaborate a remediation program with rapid automatized naming and reading, as well as to verify the clinical significance of the elaborated program for students with dyslexia. Method: The study involved five students from 3rd to the 5th grade of elementary school, aged 8 to 12 years, of both genders, with an interdisciplinary diagnosis of dyslexia. All students were submitted to pre- and post-test application of metalinguistic skills and reading test, reading comprehension and rapid automatized naming test. Results: The analysis was performed using the JT method that allowed to verify positive or negative change and clinical significance in the posttesting. The results showed clinical significance in the tests of identification, syllable addition and combination, final and medial phoneme; in addition to nonwords repetition, real words and pseudowords reading, reading comprehension and rapid automatized naming test when comparing the pre- and post-testing. Conclusion: The elaborated program was efficient and applicable as an intervention instrument based on scientific evidence for students with dyslexia since it showed clinical significance for reading performance.